Toward a Framework for a Budget Law for Economies in Transition - Allan, Bill (IMF Working Papers; Working Paper, 1994)
This paper discusses basic principles underlying budget law and reviews key features of budget legislation in several OECD countries as a basis for development of budget legislation in economies in transition to a market environment (EITs). It recommends a broad structure and a number of specific provisions that could be included in budget law for EITs.